Changes in growth performance, immune function, and meat quality of yellow-feathered broilers fed Scarabaeiform larvae meal during early-mid growth phases - Chen, Shuaihu; Liu, Tingting; Shen, Hong; Wang, Jungang (Frontiers in Veterinary Science, 2025)
Amid the global food security crisis, protein feed shortages—particularly soybean meal—severely constrain sustainable development in the livestock industry. Scarabaeiform larvae (Sl) emerge as a highly promising alternative protein source due to their nutritional and biological properties, yet their dose-stage dynamics in poultry feeding systems require systematic validation. This study evaluated replacing soybean meal with Sl meal at different doses and stages on growth performance, slaughter traits, meat quality, immune function, and gut microbiota in yellow-feathered broilers. A total of 150 one-day-old male broilers were randomly allocated into five groups: C (control, 0% Sl throughout), 4% Sl (Full) (4% Sl throughout), 8% Sl (Full) (8% Sl throughout), 4% Sl (Phased) (4% Sl from day 1–42 then 0%), and 8% Sl (Phased) (8% Sl meal from day 1–42 then 0%). The trial spanned three phases (1–21, 22–42, and 43–63 days), with slaughter sampling on day 63. During 1–42 days, the 4% Sl meal groups (4% Sl (Full), 4% Sl (Phased) groups) exhibited higher body weight and weight gain compared to controls (p < 0.05). From 43 to 63 days, 4% Sl (Phased) and 8% Sl (Phased) groups (supplemented with Sl in early-mid phases) achieved better growth performance, whereas continuous Sl supplementation (4% Sl (Full), 8% Sl (Full) groups) reduced growth rates (p < 0.05). 4% Sl (Phased) and 8% Sl (Phased) groups showed increased abdominal lipid deposition, elevated intramuscular fat (p < 0.05), and higher levels of multiple fatty acids. Immunologically, full-term Sl groups (4% Sl (Full), 8% Sl (Full) groups) had significantly higher pro-inflammatory cytokine levels (IFN-γ, IL-1β, TNF-α) than the control (p < 0.05), while 4% Sl (Phased) and 8% Sl (Phased) groups reduced this immune response (p < 0.05), and 4% Sl (Phased) group additionally increased serum IgA and IgG levels (p < 0.05). Significant differences in gut microbiota community structure were observed among groups (p < 0.05), with correlation analysis indicating that 4% Sl (Phased) group-enriched Faecalibacterium was associated with enhanced lipid deposition and regulation of antioxidant and inflammatory cytokine levels (p < 0.05). These findings demonstrate that phased 4% Sl supplementation (1–42 days) improves growth performance, intramuscular lipid deposition, and humoral immunity while mitigating excessive immune activation caused by prolonged Sl use. This strategy effectively replaces partial soybean meal in early-mid growth phases, providing a theoretical basis for the application of Sl meal in poultry feed.